The political economy of East Asia striving for wealth and power - Wan, Ming 1960- (Washington, D.C. CQ Press, 2008)
For students of international political economy, it is hard to ignore the growth, dynamism, and global impact of East Asia. Japan and China are two of the largest economies in the world, in a region now accounting for almost 30 percent more trade than the United States, Canada, and Mexico combined. What explains this increasing wealth and burgeoning power? In his new text, Ming Wan illustrates the diverse ways that the domestic politics and policies of countries within East Asia affect the region's production, trade, exchange rates, and development, and are in turn affected by global market forces and international institutions. Unlike most other texts on East Asian political economy that are essentially comparisons of major individual countries, Wan effectively integrates key thematic issues and country-specific examples to present a comprehensive overview of East Asia's role in the world economy. The text first takes a comparative look at the region's economic systems and institutions to explore their evolution - a rich and complex story that looks beyond the response to Western pressures. Later chapters are organized around close examination of production, trade, finance, and monetary relations. While featuring extended discussion of China, Japan, South Korea, and Taiwan, Wan is inclusive in his analysis, with coverage including Myanmar, Thailand, Laos, Vietnam, Cambodia, Malaysia, Singapore, Indonesia, Brunei, and the Philippines.
PART I. INTRODUCTION: 1. Introduction. What Is East Asia? -- The Political Economy Approach Design of the Book -- 2. The East Asian National Systems of Political Economy -- The Political Economy Systems of East Asia: An Overview -- The Japanese System of Political Economy -- The Political Economy Systems of the Asian Tigers -- The Political Economy Systems of Southeast Asia -- The Transitional Political Economies Conclusion -- PART II. RISE AND FALL OF EAST ASIA: 3. The Chinese World Order -- World Orders -- International Order -- Political Economy of East Asian Trade -- Comparative Political Economy -- Beyond European Models of World History -- Why Did the West Rise? -- Conclusion -- 4. Modern Imperialism -- Western Imperialism -- Japanese Imperialism -- Conclusion 5. The East Asian Miracle -- Postwar Transformation of East Asian Political Economy -- Explaining the East Asian Miracle -- A Regional Perspective of East Asian Political Economy -- The United States and East Asian Political Economy -- The Political Economy of Growth -- Conclusion -- 6. The Asian Financial Crisis -- Tracing the Crisis -- Explaining the Crisis -- Crony Capitalism -- Managing the Crisis -- The Consequences of the Crisis -- The Political Economy of the Crisis -- Conclusion -- PART III. ISSUES OF EAST ASIAN POLITICAL ECONOMY: 7. The Political Economy of East Asian Production -- The Factory of the World -- Regionalization of Production -- The East Asian State and Production -- East Asian Companies -- Domestic Political Economy of Production -- Conclusion 8. The Political Economy of East Asian Trade -- Trade Patterns in East Asia -- East Asian Trade Strategies -- Facing the World -- East Asian Trade Regionalism -- Domestic Political Economy of Trade -- Conclusion -- 9. The Political Economy of East Asian Finance -- East Asian Finance -- East Asian Financial Policies -- East Asia in Global Finance -- East Asian Financial Regionalism -- East Asian Political Economy of Finance -- Conclusion -- 10. The Political Economy of East Asian Monetary Relations -- East Asian Exchange Rate Policy -- East Asia in the Global Monetary System -- East Asian Regional Monetary System -- East Asian Political Economy of Money -- Conclusion. 11. The Political Economy of East Asian Regionalism -- Defining Regionalization and Regionalism -- East Asian Regionalization -- East Asian Regionalism Theories of Regionalism -- Political Economy of Regionalism -- Conclusion.
Keywords: East Asia -- Economic policy; East Asia -- Commercial policy; East Asia -- Foreign economic relations